SiC-based high-temperature-resistant wave-absorbing and heat-insulating aerogel and preparation method thereof

By growing SiC nanowires on SiC fiber skeleton, the problems of complex and poor controllability of multivariate composite aerogels are solved, and aerogels with high mechanical properties and high temperature wave-resistant heat insulation properties are prepared to meet aviation High temperature stealth demand for engines.

CN119118696APending Publication Date: 2024-12-13SDIC CERAMIC MATRIX COMPOSITES RES INST (XIAN) CO LTD

Patent Information

Application Number
CN202411201809.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing multi-composite aerogel preparation process is complex and the finished product is poorly controlled, which cannot meet the needs of stealth performance in high temperature environments of aircraft engines.

Method used

Using a porous SiC fiber skeleton composed of chopped SiC fibers and SiC nanowires grown on its surface, SiC nanowire pioneer solution composed of methyl trimethoxysilane, dimethyl dimethoxysilane and ethanol and short The combination of SiC fiber dispersion is cut and heat-resistant aerosol insulated aerosol is prepared through crosslinking, suction filtration, polycondensation, and carbon heat reduction.

Benefits of technology

It improves the mechanical properties and thermal stability of the aerogel, meets the infrared stealth and radar stealth needs of high-temperature components of aero engines, and has a simple preparation process and high stability of the finished product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118696A_ABST
    Figure CN119118696A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-temperature-resistant wave-absorbing material, in particular to SiC-based high-temperature-resistant wave-absorbing heat-insulating aerogel and a preparation method thereof, and aims to overcome the defects of complex process flow and poor controllability of prepared finished products of multi-component composite aerogel prepared in the prior art. The SiC-based high-temperature-resistant wave-absorbing and heat-insulating aerogel comprises a porous SiC fiber skeleton formed by chopped SiC fibers and SiC nanowires growing on the surface of the porous SiC fiber skeleton, and meanwhile, the invention provides a method for preparing the aerogel through a sol-gel combined carbon thermal reduction method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high temperature resistant wave absorbing material, and in particular to a SiC-based high temperature resistant wave absorbing heat insulating aerogel and a method for preparing the same. Background Art

[0002] The structure of high thrust-to-weight ratio aircraft engines is constantly developing in the direction of lightweight, integration and composite. Since stealth and stealth have become important performance and significant features that modern and future combat aircraft must possess, among which aircraft engine infrared stealth and radar stealth are important components of combat aircraft stealth. Therefore, the importance of achieving aircraft engine stealth effect is self-evident. With the continuous improvement of aircraft engine performance, its requirements for stealth are also increasing.

[0003] Traditional magnetic absorbing materials such as ferroferric oxide have advantages such as excellent absorbing performance and adjustable absorbing range, but they have high density and poor stability at high temperatures, so they can only be used for electromagnetic wave absorption at normal temperatures. However, with the development of all-round detection technology, the radar stealth problem of high-temperature components of aircraft needs to be solved urgently. Long-term high-temperature working conditions require not only maintaining excellent absorbing performance, but also having good oxidation resistance and corrosion resistance. At the same time, lightweight absorbing materials are also one of the necessary factors to improve the flight efficiency of combat aircraft.

[0004] In response to the demand for stealth performance in high-temperature environments of aircraft engines, corresponding technical research has been carried out both at home and abroad. The main research direction is to replace traditional magnetic absorbing materials with carbon-based, silicon-based ceramic materials and their composite materials. Among them, silicon carbide (SiC) materials have become the research focus of high-temperature absorbing materials due to their high temperature resistance, ablation resistance, good chemical stability and adjustable dielectric properties. Among them, SiC-based ceramic aerogels not only have the characteristics of low density and heat insulation, but also show better physical, chemical, mechanical and thermal stability under harsh service conditions. Moreover, ceramic aerogels based on SiC nanowires (hereinafter referred to as SiC nanowire aerogels) can be set as three-dimensional nano-network porous structures. Electromagnetic waves pass through the nano-network porous structure, thereby increasing the number of reflections and effectively improving the electromagnetic absorbing performance, making silicon carbide nanowire aerogels an electromagnetic absorbing material used in special environments. However, the SiC nanowire aerogels formed by mutual entanglement and self-assembly are only connected together by the van der Waals force and electrostatic attraction between molecules, and their mechanical properties are often poor. Up to now, multi-component composite aerogels are generally formed by doping SiC nanowire aerogels with multiple ceramic components to achieve the purposes of high temperature resistance, wave absorption and increased mechanical properties. However, multi-component composite aerogels prepared by this process often have problems with complex process flows, resulting in more impurities and defects introduced. There is also the problem of poor controllability of the finished product, which cannot be used on a large scale.

[0005] Based on the above problems, there is an urgent need to develop an aerogel that is lightweight, wave-absorbing, heat-insulating, high-temperature resistant, has a simple preparation process, and has certain mechanical properties to meet the stealth requirements in high-temperature environments such as aircraft engines. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the multi-component composite aerogel prepared in the prior art, such as complex process flow and poor controllability of the finished product, and to provide a SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel and a preparation method thereof.

[0007] To achieve the above objectives, the technical solutions provided by the present invention are as follows:

[0008] A high temperature resistant wave absorbing and heat insulating aerogel based on SiC is special in that it comprises a porous SiC fiber skeleton composed of short-cut SiC fibers and SiC nanowires grown on the surface of the porous SiC fiber skeleton.

[0009] Furthermore, the mass ratio of the chopped SiC fiber to the hydroxyethyl cellulose is 1:(1.4-1.6);

[0010] The SiC nanowires are prepared from a SiC nanowire precursor solution consisting of methyltrimethoxysilane, dimethyldimethoxysilane and ethanol.

[0011] Furthermore, the mass ratio of methyltrimethoxysilane, dimethyldimethoxysilane and ethanol is: (3.5-4.5):1:(2-20).

[0012] At the same time, the present invention also provides a method for preparing the above-mentioned SiC-based high temperature resistant wave absorbing and heat insulating aerogel, which is special in that it comprises the following steps:

[0013] Step 1, mixing a SiC nanowire precursor solution with a chopped SiC fiber dispersion to obtain a cross-linked mixed solution;

[0014] The SiC nanowire precursor solution is prepared by mixing methyltrimethoxysilane, dimethyldimethoxysilane and ethanol; the chopped SiC fiber dispersion is prepared by mixing chopped SiC fibers and an aqueous solution of hydroxyethyl cellulose;

[0015] Step 2, filtering the cross-linked mixed solution to obtain a SiC fiber skeleton with polymethylsiloxane sol attached to the surface;

[0016] Step 3, polycondensing, solidifying and drying the polymethylsiloxane sol attached to the surface of the SiC fiber skeleton to obtain a porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface;

[0017] Step 4: Carbothermal reduction treatment is performed on the polymethylsiloxane xerogel attached to the surface of the porous SiC fiber skeleton to grow SiC nanowires on the surface of the porous SiC fiber skeleton to obtain a high temperature resistant wave absorbing and heat insulating aerogel.

[0018] Further, in step 1, the length of the chopped SiC fiber is 1 to 3 mm;

[0019] The mass ratio of the SiC nanowire precursor solution to the chopped SiC fiber dispersion is (1-10):(0.5-4);

[0020] The preparation method of the chopped SiC fiber dispersion is as follows: hydroxyethyl cellulose and water are mixed evenly to obtain an aqueous solution of hydroxyethyl cellulose, chopped SiC fibers are added to the aqueous solution of hydroxyethyl cellulose, and the mixture is mixed evenly to obtain a chopped SiC fiber dispersion; wherein the mass ratio of the chopped SiC fibers, the hydroxyethyl cellulose, and the water is 1:(1.4-1.6):(35-120);

[0021] In the SiC nanowire precursor solution, the mass ratio of methyltrimethoxysilane, dimethyldimethoxysilane and ethanol is (3.5-4.5):1:(2-20).

[0022] Furthermore, in step 4, the specific process of the carbon thermal reduction treatment is as follows:

[0023] SiO2@Si mixed nanoparticles are evenly spread on the bottom of the graphite crucible, and a porous SiC fiber skeleton with polymethylsiloxane dry gel attached to the surface is covered on the SiO2@Si mixed nanoparticles. The crucible is covered with a lid, and the graphite crucible is placed in a vacuum hot pressing furnace. A constant pressure of 0.2 to 0.35 MPa is maintained in the furnace under an argon environment. The vacuum hot pressing furnace is heated to 1300 to 1600°C at a heating rate of 5 to 10°C / min and kept warm for 2 to 6 hours. The hot pressing furnace is then cooled to 600°C at a cooling rate of 2 to 5°C / min, and then naturally cooled to room temperature to complete the carbon thermal reduction treatment.

[0024] Furthermore, in step 4, the preparation method of the SiO2@Si mixed nanoparticles is: mixing silicon dioxide nanopowder and nano silicon powder in a molar ratio of 1:1 to obtain SiO2@Si mixed nanoparticles;

[0025] The mesh number of the silicon dioxide nanopowder is 100-300 meshes, and the mesh number of the nano silicon powder is 300-800 meshes; the mixing is carried out by mechanical ball milling at a speed of 300-500 r / min for 5-8 hours.

[0026] Furthermore, in step 4, the carbothermal reduction treatment further includes a step of removing free carbon, specifically:

[0027] The porous SiC fiber skeleton with SiC nanowires grown on the surface was placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, subjected to oxidation treatment for 5 hours, and then naturally cooled to room temperature to complete the removal of free carbon.

[0028] Further, step 3 is specifically: placing the SiC fiber skeleton with polymethylsiloxane sol attached to the surface in an oven at 100 to 110° C. for 4 to 6 hours to obtain a porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface;

[0029] In step 4, the carbon thermal reduction treatment is specifically as follows:

[0030] A porous SiC fiber skeleton with polymethylsiloxane dry gel attached to the surface is placed in a graphite crucible, the crucible is covered, and the graphite crucible is placed in a vacuum hot pressing furnace. A constant pressure of 0.2 to 0.35 MPa is maintained in the furnace under an argon environment. The vacuum hot pressing furnace is heated to 1300 to 1600°C at a heating rate of 5 to 10°C / min and kept warm for 2 to 6 hours. The hot pressing furnace is then cooled to 600°C at a cooling rate of 2 to 5°C / min, and then naturally cooled to room temperature to complete the carbon thermal reduction treatment.

[0031] Furthermore, in step 1, the mass ratio of methyltrimethoxysilane, dimethyldimethoxysilane and ethanol is 4:1:20;

[0032] In the chopped SiC fiber dispersion, the mass ratio of the chopped SiC fibers to hydroxyethyl cellulose water is 2:3:70.

[0033] Beneficial effects of the present invention:

[0034] 1. The present invention selects SiC material as the basic component of aerogel and adopts SiC fiber as the basic skeleton, increases the overlapping sites of SiC nanowires to enhance the mechanical properties of aerogel, avoids the slippage and deformation of SiC nanowires overlapped by intermolecular forces under the action of external forces, and improves the mechanical properties of aerogel to a certain extent compared with traditional SiC nanowire aerogel.

[0035] 2. Compared with traditional high-temperature resistant and wave-absorbing materials, the aerogel prepared by the sol-gel combined carbon thermal reduction method in the present invention has the characteristics of light weight and heat insulation, and can meet the infrared stealth and radar stealth requirements of high-temperature components of aircraft, so that the prepared aerogel retains its excellent chemical stability and high-temperature resistance while also having wave absorption and heat insulation properties.

[0036] 3. The present invention selects hydroxyethyl cellulose as the dispersant of SiC fibers, which effectively avoids the agglomeration of SiC fibers during dispersion, so that single fibers can be more evenly mixed with the precursor solution, and more cross-linked products are generated on the fiber surface.

[0037] 4. The present invention adds SiO2@Si mixed nanoparticles to participate in the carbon thermal reduction reaction at high temperature, further supplementing the silicon source required for the generation of SiC nanowires, which can effectively avoid the problem of insufficient reaction of polymethylsiloxane gel thermal decomposition to generate SiC nanowires, so that more abundant SiC nanowires are formed inside the overlapping SiC fiber skeletons.

[0038] 5. The SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel prepared by the present invention is composed of SiC, and has the significant advantages of simple preparation process, single component and stable chemical properties.

[0039] 6. After the carbon thermal reduction treatment, the present invention also provides a step of removing free carbon, and removes the remaining free carbon through oxidation treatment, thereby reducing the impurity content in the SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel and further improving the stability of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is an electron microscope (SEM) image of the cross section of the SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel prepared in Example 1 of the present invention, wherein a is an electron microscope image under a low-power microscope, and b is an electron microscope image under a high-power microscope. DETAILED DESCRIPTION

[0041] Embodiment 1

[0042] The present invention proposes a method for preparing a high temperature resistant, wave absorbing and heat insulating aerogel based on SiC. The aerogel prepared by this method uses SiC fiber as the basic skeleton, and generates a large number of SiC nanowires between the gaps of the highly porous SiC fiber skeleton. The aerogel has low density, high temperature resistance, heat insulation, wave absorption and good mechanical strength. The specific preparation method is as follows:

[0043] S1. Short cutting of SiC fibers

[0044] The SiC fiber bundle was cut into short SiC fibers with a length of 1 to 3 mm, and the surface dust was cleaned by ultrasonic cleaning with an ethanol solution, and the fibers were placed in a constant temperature box at 80°C to dry for later use.

[0045] The chopped SiC fibers can be better dispersed in the solution and form a three-dimensional skeleton after filtration, providing space for the growth of SiC nanowires.

[0046] In this embodiment, the SiC fiber bundle is Japanese Tyranno SA fiber, which includes 1600 fibers, each of which has an average diameter of 10 μm, a C / Si atomic ratio in the range of 0.92 to 0.95, a temperature resistance of 1800° C., and a length of 2 mm for the chopped SiC fibers.

[0047] In other embodiments of the present invention, SiC fiber bundles of different specifications may also be selected as needed.

[0048] S2. Configuration of chopped SiC fiber dispersion

[0049] The dispersant hydroxyethyl cellulose and water are mixed in a certain mass ratio, and magnetically stirred at a speed of 600 to 800 r / min for 15 to 30 minutes to obtain an aqueous solution of hydroxyethyl cellulose. Subsequently, the solution speed is reduced to 300 to 500 r / min, and the chopped SiC fibers obtained by S1 are slowly added to the aqueous solution of hydroxyethyl cellulose, and magnetic stirring is continued for 15 to 30 minutes to make it evenly mixed, thereby completing the configuration of the chopped SiC fiber dispersion.

[0050] The mass ratio of the chopped SiC fiber, hydroxyethyl cellulose and water can be 2:3:(70-240).

[0051] In this embodiment, magnetic stirring is performed at a speed of 600 r / min for 30 minutes to obtain an aqueous solution of hydroxyethyl cellulose, and then the solution speed is reduced to 300 r / min and magnetic stirring is continued for 30 minutes; the mass ratio of chopped SiC fibers, hydroxyethyl cellulose, and water is 1:1.5:120.

[0052] S3. Configuration of SiC nanowire precursor solution

[0053] Methyltrimethoxysilane (MTMS), dimethyldimethoxysilane (DMDMS) and ethanol (EtOH) are mixed in a mass ratio of 4:1:(2-20), and magnetically stirred for 30-60 minutes to make them uniformly mixed to obtain a siloxane sol ethanol solution as a SiC nanowire precursor solution.

[0054] When preparing the SiC nanowire precursor solution, ethanol is added and the viscosity of the SiC nanowire precursor solution is adjusted by adjusting the amount of ethanol added to meet the range of 1.85 to 6.03 mPa·s.

[0055] In this embodiment, the mass ratio of MTMS, DMDMS and EtOH is 4:1:2, and magnetic stirring is performed for 30 minutes. The viscosity of the obtained SiC nanowire precursor solution is 6.03 mPa·s.

[0056] Preparation of S4 and SiO2@Si mixed nanoparticles

[0057] The silicon dioxide nanopowder with a mesh size of 100 to 300 meshes and the nano silicon powder with a mesh size of 300 to 800 meshes are mixed in a molar ratio of 1:1, and the mixture is ball-milled at a speed of 300 to 500 r / min for 5 to 8 hours to obtain SiO2@Si mixed nanoparticles.

[0058] In this embodiment, the mesh sizes of the silicon dioxide nanopowder and the nano-silicon powder are 200 mesh and 500 mesh, respectively, and the mechanical ball milling is performed at a speed of 500 r / min for 5 hours.

[0059] S5. Preparation of porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface

[0060] The SiC nanowire precursor solution in S3 and the chopped SiC fiber dispersion in S2 are mixed in a mass ratio of (1-10):(0.5-4), and magnetically stirred at a speed of 500-800 r / min for 30-60 minutes to obtain a cross-linked mixed solution, which is added into a vacuum filtration mold, and filtered through the vacuum filtration mold to obtain a SiC fiber skeleton with polymethylsiloxane sol attached to the surface, and the SiC fiber skeleton is made to have an ideal size and shape through the vacuum filtration mold.

[0061] The obtained SiC fiber skeleton with polymethylsiloxane sol attached to the surface is treated in an oven at 100-110°C for 4-6 hours. During this process, the polymethylsiloxane sol attached to the surface of the SiC fiber undergoes polycondensation and coagulation, and is converted into a siloxane gel. The siloxane gel is then dried to obtain a density of 0.17-0.27 g / cm 3 A porous SiC fiber skeleton with polymethylsiloxane xerogel is attached to the surface.

[0062] In this embodiment, the mass ratio of the SiC nanowire precursor solution to the chopped SiC fiber dispersion in S2 is 6:3.5, and the mixture is magnetically stirred at a speed of 800 r / min for 60 minutes to obtain a cross-linked mixed solution; the SiC fiber skeleton with polymethylsiloxane sol attached to the surface is treated in an oven for 5 hours; the obtained porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface has a density of 0.27 g / cm 3 .

[0063] S6. Carbothermal reduction treatment

[0064] 5-10 g of SiO2@Si mixed nanoparticles are evenly spread on the bottom of a graphite crucible, and the porous SiC fiber skeleton with polymethylsiloxane dry gel attached to the surface obtained in S5 is covered on the SiO2@Si mixed nanoparticles. The crucible is covered with a lid, and the graphite crucible is placed in a vacuum hot pressing furnace. A constant pressure of 0.2-0.35 MPa is maintained in the furnace under an argon environment. The vacuum hot pressing furnace is heated to 1300-1600°C at a heating rate of 5-10°C / min and kept warm for 2-6 hours. During this period, the amorphous polymethylsiloxane dry gel attached to the fiber surface of the porous SiC fiber skeleton is decomposed to generate CO and SiO gas, and the SiO2@Si mixed nanoparticles undergo a neutralization reaction to generate SiO gas. CO and SiO undergo a carbothermal reduction reaction, and a large number of SiC nanowires are nucleated on the fiber surface inside the porous SiC fiber skeleton and grow in situ. Subsequently, the vacuum hot pressing furnace was cooled to 600°C at a cooling rate of 2 to 5°C / min, and then naturally cooled to room temperature to complete the carbon thermal reduction treatment to obtain a high-temperature resistant, wave-absorbing and heat-insulating aerogel based on SiC.

[0065] In step S6, after cooling to room temperature, an oxidation decarbonization treatment is also included to remove free carbon, specifically: the porous SiC fiber skeleton with a large number of SiC nanowires grown is placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, and subjected to an oxidation treatment for 5 hours to remove the residual free carbon inside, and then naturally cooled to room temperature to complete the oxidation decarbonization treatment. The present invention finally obtains a high-temperature resistant, wave-absorbing, and heat-insulating aerogel based on SiC with an average density of 5 to 40 mg / cm 3 , and its performance parameters are shown in Table 1.

[0066]

[0067] In step S6 of this embodiment, 5 g of SiO2@Si mixed nanoparticles are evenly spread on the bottom of the graphite crucible, the pressure in the furnace is 0.2 MPa, the temperature is increased to 1300°C at a heating rate of 10°C / min, and the temperature is kept for 2 hours. Subsequently, the hot pressing furnace is cooled to 600°C at a cooling rate of 5°C / min; in the oxidation and decarbonization treatment, the temperature is increased to 700°C at a heating rate of 5°C / min, and the oxidation treatment is carried out for 5 hours; the high temperature resistant wave absorbing and heat insulating aerogel finally obtained in this embodiment has a density of 40 mg / cm 3 , the thermal conductivity at room temperature is 0.26w / (mk), the thermal conductivity at 1100℃ is 0.43w / (mk), and the X-band is -10dB.

[0068] The present invention provides sufficient SiO gas by arranging SiO2@Si mixed nanoparticles to efficiently promote the reaction. In other embodiments of the present invention, only the porous SiC fiber skeleton with polymethylsiloxane dry gel attached to the surface can be placed in a graphite crucible for carbon thermal reduction treatment.

[0069] The molecular structure of the dispersant hydroxyethyl cellulose of the present invention contains more polar hydroxyl groups, which can form hydrogen bonds with hydrophobic functional groups such as hydrocarbon CH and carbonyl CO on the surface of the chopped SiC fiber and water molecules, thereby enhancing the hydrophilicity and wetting of the SiC fiber surface, and promoting the chopped SiC fiber to be evenly dispersed in water in a single-filament state, thereby improving the dispersibility and stability of the carbon fiber, and further enabling a single chopped SiC fiber to be more evenly mixed with the precursor solution, thereby generating more cross-linked products on the surface of the chopped SiC fiber, and finally generating more SiC nanowires, which helps to improve the mechanical strength, toughness and high temperature resistance of the high temperature resistant wave absorbing and heat insulating aerogel. Hydroxyethyl cellulose gradually decomposes at a temperature of 400°C, and the products are mainly CO and water, and the decomposed CO can provide a carbon source to promote the generation of SiC nanowires, so it is an ideal SiC fiber dispersant of the present invention.

[0070] The higher the viscosity of the SiC nanowire precursor solution, the more SiC nanowire precursor solution is retained by filtration, resulting in more SiC nanowires generated in the end, and the higher the proportion of the SiC nanowire precursor solution, the more SiC nanowires are generated in the end; conversely, the fewer SiC nanowires are generated. When the space formed by the porous SiC fiber skeleton is sufficient to meet the growth and extension of SiC nanowires, the density of the high-temperature absorbing and heat-insulating aerogel will increase with the increase in the growth of SiC nanowires, resulting in an increase in its thermal conductivity value, thereby reducing the overall thermal insulation performance and high-temperature resistance performance; conversely, the density decreases and the thermal conductivity value decreases, thereby improving the overall thermal insulation performance and high-temperature resistance performance of the aerogel. At the same time, the wave absorption performance is also an important indicator for evaluating the performance of the aerogel. When the number of SiC nanowires is less than a certain number, the wave absorption performance will be reduced. Therefore, the present invention sets a specific viscosity of the SiC nanowire precursor solution and a ratio of the SiC nanowire precursor solution to the chopped SiC fiber dispersion. The two cooperate with each other to make the final high-temperature resistant wave absorbing and heat insulating aerogel have a suitable density, thereby satisfying the thermal conductivity, wave absorption, heat insulation and high temperature resistance performances at the same time.

[0071] The porous SiC fiber skeleton of the present invention is formed by freely overlapping short-cut SiC fibers after filtration, and its structure is diverse, and different external dimensions can be designed according to product requirements; the present invention provides reaction sites for SiC nanowires through the porous SiC fiber skeleton, and nanowires can be generated on the surface of the outside of the skeleton composed of short-cut SiC fibers and the surface inside the skeleton space, so that the finally obtained SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel is composed of a large number of SiC nanowires that are entangled with each other and well connected, and its composition is single and its physical and chemical properties are stable; the present invention uses SiC fiber as a basic skeleton, which has a certain load-bearing effect. Compared with aerogels composed only of nanowires, the SiC fiber skeleton can enhance the mechanical properties of the high-temperature resistant wave-absorbing and heat-insulating aerogel, and avoids the slippage and deformation of the SiC nanowires overlapped by intermolecular forces under the action of external forces.

[0072] Embodiment 2

[0073] The present invention provides a method for preparing a high temperature resistant wave absorbing and heat insulating aerogel based on SiC, comprising the following steps:

[0074] S1. Short cutting of SiC fibers

[0075] The SiC fiber bundle was cut into short fibers with a length of 2 mm. The surface dust was cleaned by ultrasonic cleaning with an ethanol solution and dried in a thermostat at 80°C for later use.

[0076] In this embodiment, the SiC fiber bundle is Japanese Tyranno SA fiber.

[0077] S2. Configuration of chopped SiC fiber dispersion

[0078] Hydroxyethyl cellulose was mixed with water and magnetically stirred at a speed of 600 r / min for 30 minutes. Subsequently, the solution speed was reduced to 300 r / min, and the chopped SiC fibers obtained by S1 were slowly added to the aqueous solution of hydroxyethyl cellulose, and magnetic stirring was continued for 30 minutes to complete the dispersion of the chopped SiC fibers. Among them, the mass ratio of chopped SiC fibers, hydroxyethyl cellulose, and water was 1:1.5:75.

[0079] S3. Preparation of silicon carbide nanowire precursor solution

[0080] MTMS, DMDMS and EtOH were mixed in a mass ratio of 4:1:8, and magnetically stirred for 30 minutes to make them uniformly mixed, thereby obtaining a siloxane sol ethanol solution as a SiC nanowire precursor solution, and the viscosity of the siloxane sol ethanol solution was 2.36 mPa·s.

[0081] Preparation of S4 and SiO2@Si mixed nanoparticles

[0082] Silica nanopowder with a mesh size of 200 mesh and nano-silicon powder with a mesh size of 500 mesh were mixed in a molar ratio of 1:1, and ball-milled at a speed of 500 r / min for 5 hours by mechanical ball milling to obtain SiO2@Si mixed nanoparticles.

[0083] S5. Preparation of porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface

[0084] The SiC nanowire precursor solution in S3 and the chopped SiC fiber dispersion in S2 were mixed in a mass ratio of 7:3, and magnetically stirred at a speed of 800 r / min for 60 minutes to obtain a cross-linked mixed solution, which was added into a vacuum filtration mold to obtain a SiC fiber skeleton with an ideal size and shape and a polymethylsiloxane sol attached to the surface.

[0085] The SiC fiber skeleton with polymethylsiloxane sol attached to the surface was treated in an oven at 100 °C for 5 h to obtain a density of 0.21 g / cm 3 A porous SiC fiber skeleton with polymethylsiloxane xerogel is attached to the surface.

[0086] S6. Carbothermal reduction treatment

[0087] 8g of SiO2@Si mixed nanoparticles were evenly spread on the bottom of the graphite crucible, and the porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface obtained in S5 was covered on the top of the SiO2@Si mixed nanoparticles, and the crucible was covered. The graphite crucible was placed in a vacuum hot press furnace, and a constant pressure of 0.2MPa was maintained in the furnace under an argon environment. The vacuum hot press furnace was heated to 1500℃ at a heating rate of 10℃ / min and kept warm for 4 hours. A large number of SiC nanowires were in situ grown on the fiber surface inside the porous SiC fiber skeleton. Subsequently, the vacuum hot press furnace was cooled to 600℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature.

[0088] S7, Oxidation and Carbon Removal Treatment

[0089] The porous SiC fiber skeleton with a large number of SiC nanowires grown was placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, and subjected to oxidation treatment for 5 hours, and then naturally cooled to room temperature to complete the oxidation and carbon removal treatment to obtain a SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel. The density of the SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel obtained in this embodiment is 18 mg / cm 3 , the room temperature thermal conductivity is 0.10w / (mk), the 1100℃ thermal conductivity is 0.18w / (mk), and the X-band is -10dB, as shown in Table 2.

[0090]

[0091] The results obtained by observing the cross section of the SiC-based high temperature resistant wave absorbing and heat insulating aerogel in this embodiment using an electron microscope (SEM) are as follows: Figure 1 As shown, Figure 1 It can be seen from a that the thicker SiC fibers overlap each other to form a skeleton, and many thin SiC nanowires are generated around it. Further magnification of the electron microscope, under high magnification, from Figure 1 From b, we can see that the SiC nanowires overlap and entangle with each other and have a large aspect ratio. This structure has the advantages of light weight, high temperature resistance, and excellent wave absorbing performance.

[0092] Embodiment 3

[0093] The present invention provides a method for preparing a high temperature resistant wave absorbing and heat insulating aerogel based on SiC, comprising the following steps:

[0094] S1. Short cutting of SiC fibers

[0095] The SiC fiber bundle was cut into short fibers with a length of 2 mm. The surface dust was cleaned by ultrasonic cleaning with an ethanol solution and dried in a thermostat at 80°C for later use.

[0096] In this embodiment, the SiC fiber bundle is Japanese Tyranno SA fiber.

[0097] S2. Configuration of chopped SiC fiber dispersion

[0098] Hydroxyethyl cellulose was mixed with water and magnetically stirred at a speed of 600 r / min for 30 minutes. Subsequently, the solution speed was reduced to 300 r / min, and the chopped SiC fibers obtained by S1 were slowly added to the aqueous solution of hydroxyethyl cellulose, and magnetic stirring was continued for 30 minutes to complete the dispersion of the chopped SiC fibers. Among them, the mass ratio of chopped SiC fibers, hydroxyethyl cellulose, and water was 1:1.5:120.

[0099] S3. Preparation of SiC nanowire precursor solution

[0100] MTMS, DMDMS and EtOH were mixed in a mass ratio of 4:1:20, and magnetically stirred for 30 minutes to make them uniformly mixed, to obtain a siloxane sol ethanol solution as a SiC nanowire precursor solution, and the viscosity of the siloxane sol ethanol solution was 1.85 mPa·s.

[0101] Preparation of S4 and SiO2@Si mixed nanoparticles

[0102] Silica nanopowder with a mesh size of 200 mesh and nano-silicon powder with a mesh size of 500 mesh were mixed in a molar ratio of 1:1, and ball-milled at a speed of 500 r / min for 5 hours by mechanical ball milling to obtain SiO2@Si mixed nanoparticles.

[0103] S5. Preparation of porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface

[0104] The SiC nanowire precursor solution in S3 and the chopped SiC fiber dispersion in S2 were mixed in a mass ratio of 10:0.5, and magnetically stirred at a speed of 800 r / min for 60 minutes to obtain a cross-linked mixed solution, which was added into a vacuum filtration mold to obtain a SiC fiber skeleton with an ideal size and shape and a polymethylsiloxane sol attached to the surface.

[0105] The SiC fiber skeleton with polymethylsiloxane sol attached to the surface was treated in an oven at 100 °C for 5 h to obtain a density of 0.17 g / cm 3 A porous SiC fiber skeleton with polymethylsiloxane xerogel is attached to the surface.

[0106] S6. Carbothermal reduction treatment

[0107] 10g SiO2@Si mixed nanoparticles were evenly spread on the bottom of the graphite crucible, and the porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface obtained in S5 was covered on the top of the SiO2@Si mixed nanoparticles, and the crucible was covered. The graphite crucible was placed in a vacuum hot press furnace, and a constant pressure of 0.2MPa was maintained in the furnace under an argon environment. The vacuum hot press furnace was heated to 1300℃ at a heating rate of 10℃ / min and kept warm for 2 hours. A large number of SiC nanowires were in situ grown on the fiber surface inside the porous SiC fiber skeleton. Subsequently, the vacuum hot press furnace was cooled to 600℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature.

[0108] S7, Oxidation and Carbon Removal Treatment

[0109] The porous SiC fiber skeleton with a large number of SiC nanowires grown was placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, and subjected to oxidation treatment for 5 hours, and then naturally cooled to room temperature to complete the oxidation and carbon removal treatment to obtain a SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel. The density of the SiC-based high-temperature resistant wave-absorbing and heat-insulating aerogel obtained in this embodiment is 5 mg / cm 3 , the thermal conductivity at room temperature is 0.08w / (mk), the thermal conductivity at 1100℃ is 0.15w / (mk), and the X-band is -8dB.

[0110] Embodiment 4

[0111] The difference between this embodiment and the second embodiment is that in step S2, the mass ratio of chopped SiC fiber, hydroxyethyl cellulose and water is 1:1.5:35, and in step S3, the mass ratio of MTMS, DMDMS and EtOH is 3.5:1:20, and the rest of the contents are the same.

[0112] Embodiment 5

[0113] The difference between this embodiment and the second embodiment is that in step S3, the mass ratio of MTMS, DMDMS and EtOH is 4.5:1:15, and in step S5, the SiC nanowire precursor solution and the chopped SiC fiber dispersion are mixed in a mass ratio of 1:3, and the rest of the contents are the same.

Claims

1. A high temperature resistant wave absorbing and heat insulating aerogel based on SiC, Features: The invention comprises a porous SiC fiber skeleton composed of short-cut SiC fibers and SiC nanowires grown on the surface of the porous SiC fiber skeleton.

2. According to claim 1, a SiC-based high temperature resistant wave absorbing and heat insulating aerogel, Features: The mass ratio of the chopped SiC fiber to the hydroxyethyl cellulose is 1:(1.4-1.6); The SiC nanowires are prepared from a SiC nanowire precursor solution consisting of methyltrimethoxysilane, dimethyldimethoxysilane and ethanol.

3. According to claim 2, a SiC-based high temperature resistant wave absorbing and heat insulating aerogel, Features: The mass ratio of the methyltrimethoxysilane, dimethyldimethoxysilane and ethanol is: (3.5-4.5):1:(2-20).

4. A method for preparing the high temperature resistant wave absorbing and heat insulating aerogel based on SiC according to any one of claims 1 to 3, It is characterized in that The following steps are involved: Step 1, mixing a SiC nanowire precursor solution with a chopped SiC fiber dispersion to obtain a cross-linked mixed solution; The SiC nanowire precursor solution is prepared by mixing methyltrimethoxysilane, dimethyldimethoxysilane and ethanol; the chopped SiC fiber dispersion is prepared by mixing chopped SiC fibers and an aqueous solution of hydroxyethyl cellulose; Step 2, filtering the cross-linked mixed solution to obtain a SiC fiber skeleton with polymethylsiloxane sol attached to the surface; Step 3, polycondensing, solidifying and drying the polymethylsiloxane sol attached to the surface of the SiC fiber skeleton to obtain a porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface; Step 4: Carbothermal reduction treatment is performed on the polymethylsiloxane xerogel attached to the surface of the porous SiC fiber skeleton to grow SiC nanowires on the surface of the porous SiC fiber skeleton to obtain a high temperature resistant wave absorbing and heat insulating aerogel.

5. A method for preparing a high temperature resistant, wave absorbing and heat insulating aerogel based on SiC according to claim 4, Features: In step 1, the length of the chopped SiC fiber is 1 to 3 mm; The mass ratio of the SiC nanowire precursor solution to the chopped SiC fiber dispersion is (1-10):(0.5-4); The preparation method of the chopped SiC fiber dispersion is as follows: hydroxyethyl cellulose and water are mixed evenly to obtain an aqueous solution of hydroxyethyl cellulose, chopped SiC fibers are added to the aqueous solution of hydroxyethyl cellulose, and the mixture is mixed evenly to obtain a chopped SiC fiber dispersion; wherein the mass ratio of the chopped SiC fibers, the hydroxyethyl cellulose, and the water is 1:(1.4-1.6):(35-120); In the SiC nanowire precursor solution, the mass ratio of methyltrimethoxysilane, dimethyldimethoxysilane and ethanol is (3.5-4.5):1:(2-20).

6. A method for preparing a high temperature resistant, wave absorbing and heat insulating aerogel based on SiC according to claim 5, Features: In step 4, the specific process of the carbon thermal reduction treatment is: Evenly spread SiO on the bottom of the graphite crucible 2 @Si hybrid nanoparticles, a porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface is covered with SiO 2 @Si mixed nanoparticles, put the crucible cover on it, place the graphite crucible in a vacuum hot pressing furnace, maintain a constant pressure of 0.2-0.35MPa in the furnace under an argon environment, heat the vacuum hot pressing furnace to 1300-1600℃ at a heating rate of 5-10℃ / min, and keep it warm for 2-6 hours, then cool the hot pressing furnace to 600℃ at a cooling rate of 2-5℃ / min, and then naturally cool to room temperature to complete the carbon thermal reduction treatment.

7. A method for preparing a high temperature resistant, wave absorbing and heat insulating aerogel based on SiC according to claim 6, Features: In step 4, the SiO 2 The preparation method of Si mixed nanoparticles is as follows: SiO nanopowder and nano silicon powder are mixed uniformly in a molar ratio of 1:1 to obtain SiO 2 @Si hybrid nanoparticles; The mesh number of the silicon dioxide nanopowder is 100-300 meshes, and the mesh number of the nano silicon powder is 300-800 meshes; the mixing is carried out by mechanical ball milling at a speed of 300-500 r / min for 5-8 hours.

8. A method for preparing a high temperature resistant, wave absorbing and heat insulating aerogel based on SiC according to any one of claims 4 to 7, It is characterized in that In step 4, the carbothermal reduction treatment further includes a step of removing free carbon, specifically: The porous SiC fiber skeleton with SiC nanowires grown on the surface was placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, subjected to oxidation treatment for 5 hours, and then naturally cooled to room temperature to complete the removal of free carbon.

9. A method for preparing a high temperature resistant, wave absorbing and heat insulating aerogel based on SiC according to claim 8, Features: Step 3 is specifically: placing the SiC fiber skeleton with polymethylsiloxane sol attached to the surface in an oven at 100-110° C. for 4-6 hours to obtain a porous SiC fiber skeleton with polymethylsiloxane xerogel attached to the surface; In step 4, the carbon thermal reduction treatment is specifically as follows: A porous SiC fiber skeleton with polymethylsiloxane dry gel attached to the surface is placed in a graphite crucible, the crucible is covered, and the graphite crucible is placed in a vacuum hot pressing furnace. A constant pressure of 0.2 to 0.35 MPa is maintained in the furnace under an argon environment. The vacuum hot pressing furnace is heated to 1300 to 1600°C at a heating rate of 5 to 10°C / min and kept warm for 2 to 6 hours. The hot pressing furnace is then cooled to 600°C at a cooling rate of 2 to 5°C / min, and then naturally cooled to room temperature to complete the carbon thermal reduction treatment.

10. A method for preparing a high temperature resistant, wave absorbing and heat insulating aerogel based on SiC according to claim 9, Features: In step 1, the mass ratio of methyltrimethoxysilane, dimethyldimethoxysilane and ethanol is 4:1:20; In the chopped SiC fiber dispersion, the mass ratio of the chopped SiC fibers to hydroxyethyl cellulose water is 2:3:70.

Citation Information

Patent Citations

  • Nanowire constructed SiC elastic ceramic and preparation method thereof

    CN107188527A

  • In-situ growth SiC nanowire reinforced SiC ceramic matrix composite material and preparation method thereof

    CN107903067A

  • Method for in-situ growth of silicon carbide nanowire on surface of silicon carbide fiber

    CN112030544A

Cited By

  • SiC composite aerogel-based electromagnetic wave-absorbing material and preparation method thereof

    CN122102131A